Gli scandali di una «ninfetta con la frangia lunga». Catherine Spaak nei primi anni Sessanta (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
Between 1960 and 1964 the name Catherine Spaak became synonymous of scandal. Her transgressive roles on the screen, the eroticism of her teenage body and her personal life were considered outrageous for the time. This essay aims to investigate Spaak’s stardom in the early Sixties, in particular some scandals during the first part of her career. Specifically, this article aims to reconstruct her personal events through the study of some texts, including thirty magazine articles collected in the database of the research project “Comizi d’amore. Il cinema e la questione sessuale in Italia (1948‐1978)”.
Keywords: Catherine Spaak; stardom; star scandals; Italian cinema; sexuality